Comparative Evaluation of Machine Learning Approaches for Predicting Optimal Parameters in Cold Metal Transfer Welding of Aluminum 8000 Series - Yajat Kapur, Mrigank Gupta, Mohit Nebhnani, Reeta Wattal (Journal of Neonatal Surgery, 2025)
Cold Metal Transfer (CMT) welding is an advanced gas metal arc welding (GMAW) technique characterized by its low heat input, spatter-free arc, and precise control over metal deposition. Unlike conventional MIG/MAG welding, CMT separates the wire feeding and current control systems, enabling controlled short-circuit transfer, making it ideal for joining thin and dissimilar materials such as aluminum and magnesium alloys. This study explores the application of machine learning (ML) models—Random Forest, K-Nearest Neighbors (KNN), and Gaussian Process Regression (GPR)—to predict optimal CMT welding parameters (voltage, current, wire feed rate) based on the chemical composition of aluminum alloys. The goal is to achieve target Ultimate Tensile Strength (UTS) while minimizing experimental trials. A benchmark datapoint from aluminum 8011 was used to evaluate model accuracy, and all models were assessed using performance metrics such as Root Mean Squared Error (RMSE) and Mean Absolute Percentage Error (MAPE). Results showed that GPR and Random Forest provided highly accurate, interpretable predictions. This work contributes to the development of a data-driven, inverse modeling framework for smart welding systems, enabling rapid parameter optimization across a wide range of aluminum alloys. Cold Metal Transfer (CMT) welding is an advanced gas metal arc welding (GMAW) technique characterized by its low heat input, spatter-free arc, and precise control over metal deposition. Unlike conventional MIG/MAG welding, CMT separates the wire feeding and current control systems, enabling controlled short-circuit transfer, making it ideal for joining thin and dissimilar materials such as aluminum and magnesium alloys. This study explores the application of machine learning (ML) models—Random Forest, K-Nearest Neighbors (KNN), and Gaussian Process Regression (GPR)—to predict optimal CMT welding parameters (voltage, current, wire feed rate) based on the chemical composition of aluminum alloys. The goal is to achieve target Ultimate Tensile Strength (UTS) while minimizing experimental trials. A benchmark datapoint from aluminum 8011 was used to evaluate model accuracy, and all models were assessed using performance metrics such as Root Mean Squared Error (RMSE) and Mean Absolute Percentage Error (MAPE). Results showed that GPR and Random Forest provided highly accurate, interpretable predictions. This work contributes to the development of a data-driven, inverse modeling framework for smart welding systems, enabling rapid parameter optimization across a wide range of aluminum alloys.